Pengaruh Penerapan Golden Ratio Dalam Desain Kalender Terhadap Persepsi Visual, Pemahaman Pesan, dan Sikap Karyawan PT JICT - Afifah, Rifdah Afnan ‘; Suwanda, Bayu Suriaatmaja; Fahrurrizal, Fikry (Publikasi Indonesia, 2025)
This research aims to examine the effectiveness of applying the Golden Ratio principle in the design of the 2025 company calendar of PT JICT as a visual communication medium. A quantitative approach with simple linear regression was used, involving 96 permanent employees of PT JICT as respondents. Data collection was conducted through a four-point Likert scale questionnaire, which was then transformed from an ordinal scale to an interval scale using the Method of Successive Interval (MSI). The results indicate that the application of the Golden Ratio significantly influences the effectiveness of visual communication, particularly in visual perception, improving message comprehension, employee attitudes, and reinforcing the company's identity. This study is based on visual communication theory by Lester (2022) and quantitative methodology by Creswell (2014).